A Study On The Flatness Control Of High Hardness Thin Plate In Quenching Process - Heedong Sung; Minho Park; Sunyoung Choi; Boryong Lee (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
Recently, the demand for ultra-thin steel plate with high hardness and strength has been increasing in various industries. In order to satisfy this requirement, steel company designs the chemistry with low CEQ and obtains the required characteristics through quenching and tempering process. Especially, these steels are accompanied by low temperature tempering as a necessary process. Unlike ordinary high temperature tempering steels, it is impossible to improve the flatness after low temperature tempering. Therefore, shape control in the quenching process is very important for securing the excellent quality flatness. In order to obtain flatness in the quenching process, uniform cooling inside the plate should be accompanied. However, the quenching process has limitations in estimating the temperature behavior during cooling because the plate temperature is lowered to room temperature. In this study, a thermocouple was installed inside the actual quenching plate to measure the temperature behavior during cooling and to establish the manufacturing conditions of the quenching plate to ensure excellent flatness quality.